Euglycemic Ketoacidosis in a non-diabetic patient: a rare adverse effect of sodium-glucose co-transporter type-2 inhibitors. A review based on a case report - Francisca Fonseca; Ana Piedade; Beatriz Mendes; António Inácio; Ricardo Pereira; Mónica Corte-Real; Elsa Soares; Joana Carreira; Karina Soto (Nefrología Latinoamericana)
Sodium-glucose co-transporter type-2 (SGLT-2) inhibitors (SGLT2i) are increasingly used in clinical practice, with proven benefits in chronic conditions such as diabetes mellitus, heart failure (HF), and chronic kidney disease. Prescription of SGLT2i is a common practice among healthcare providers. It is imperative that clinicians can identify and prevent adverse effects of these drugs. Euglycemic ketoacidosis (eKA) is a rare and potentially serious adverse effect of SGLT2i in patients with diabetes; recent reports indicate that this can also occur in non-diabetic patients. We present the case of an elderly non-diabetic female patient who was treated with SGLT2i for HF and developed eKA.